2018
DOI: 10.1177/1120700018779886
|View full text |Cite
|
Sign up to set email alerts
|

The effect of altering head length on corrosion using a material loss method

Abstract: In contrast to studies using qualitative methodologies, there was no correlation between head length and material loss when confined to a 28-mm head. Broad application of this outcome should be cautioned against as this study examined 1 taper construct and a metal-on-polyethylene articulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Presuming that metal ion levels are a reliable indicator of taper corrosion, our results support the findings of a series of retrieval studies which have not found any association between taper corrosion and head size. 19,24,29,32,33 In contrast, other studies have associated larger metal heads with taper fretting and corrosion. 11,12,23 Since large heads may increase stress on the head-neck junction, 15 one would expect them to associate with taper corrosion-related complications, like the higher risk of revision due to adverse reaction to metal debris observed in ⩾36-mm metal-oncross-linked polyethylene bearings in the Australian registry.…”
Section: Discussionmentioning
confidence: 96%
“…Presuming that metal ion levels are a reliable indicator of taper corrosion, our results support the findings of a series of retrieval studies which have not found any association between taper corrosion and head size. 19,24,29,32,33 In contrast, other studies have associated larger metal heads with taper fretting and corrosion. 11,12,23 Since large heads may increase stress on the head-neck junction, 15 one would expect them to associate with taper corrosion-related complications, like the higher risk of revision due to adverse reaction to metal debris observed in ⩾36-mm metal-oncross-linked polyethylene bearings in the Australian registry.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, increased head offset has been implicated as a cause of corrosion due to the increased varus load on the taper 8 . However, there is mixed evidence in the literature, and the relationship between head offset and corrosion remains unclear 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Unworn areas can readily be identified using visual inspection [19,57], observing regions with evidence of original machining marks, or which are known to have not been in mechanical contact [101]. This process has been noted to improve when using SEM [49] and optical microscopy [21] over standard visual inspection.…”
Section: Unworn Region and Engagementmentioning
confidence: 99%